Importance of fish gender as a factor in environmental monitoring of mercury - Jankovská, Ivana; Miholová, Daniela; Romočuský, Stěpán; Petrtýl, Miloslav; Langrová, Iva; Kalous, Lukáš; Sloup, Vladislav; Válek, Petr; Vadlejch, Jaroslav; Lukešová, Daniela (Environmental science and pollution research international, 2014)
Total mercury concentrations were determined in the gonadal tissues of 15 female and 10 male European perch (Perca fluviatilis) from one location of the stream "Jevanský potok" located about 30 km from Prague (Czech Republic). Tissue samples were frozen at -26 °C in polypropylene containers until further processing, which was carried out using an Advance Mercury Analyser (single purpose atomic absorption spectrometer). Mercury concentrations were present in all analysed gonad samples, and ranged from 2.3 to 12.7 μg/kg wet weight. However, we determined a mean Hg concentration (9.45 μg/kg) in male gonads that was 2.4 times greater than that of female gonads (3.9 μg/kg). This is an important finding when taking into account fish sex in environmental pollution monitoring (especially for mercury contamination).
Keywords: chemické látky znečišťující vodu; Environmental Monitoring; Male; monitorování životního prostředí; sexuální faktory; Česká republika; Gonads; rtuť; řeky; Water Pollutants, Chemical; Mercury; mužské pohlaví; Rivers; ryby; Czech Republic; Fishes; Animals; ženské pohlaví; zvířata; Sex Factors; Female; gonády